The role of age and exposure to Plasmodium falciparum in the rate of acquisition of naturally acquired immunity: a randomized controlled trial. - Caterina Guinovart; Carlota Dobaño; Quique Bassat; Augusto Nhabomba; Llorenç Quintó; Maria Nélia Manaca; Ruth Aguilar; Mauricio H Rodríguez; Arnoldo Barbosa; John J Aponte; Alfredo G Mayor; Montse Renom; et al. (PLoS ONE, 2012)
Background The rate of acquisition of naturally acquired immunity (NAI) against malaria predominantly depends on transmission intensity and age, although disentangling the effects of these is difficult. We used chemoprophylaxis to selectively control exposure to P. falciparum during different periods in infancy and explore the effect of age in the build-up of NAI, measured as risk of clinical malaria. Methods and findings A three-arm double-blind randomized placebo-controlled trial was conducted in 349 infants born to Mozambican HIV-negative women. The late exposure group (LEG) received monthly Sulfadoxine-Pyrimethamine (SP) plus Artesunate (AS) from 2.5-4.5 months of age and monthly placebo from 5.5-9.5 months; the early exposure group (EEG) received placebo from 2.5-4.5 months and SP+AS from 5.5-9.5 months; and the control group (CG) received placebo from 2.5-9.5 months. Active and passive case detection (PCD) were conducted from birth to 10.5 and 24 months respectively. The primary endpoint was time to first or only episode of malaria in the second year detected by PCD. The incidence of malaria during the second year was of 0.50, 0.51 and 0.35 episodes/PYAR in the LEG, EEG and CG respectively (p = 0.379 for the adjusted comparison of the 3 groups). The hazard ratio of the adjusted comparison between the LEG and the CG was 1.38 (0.83-2.28, p = 0.642) and that between the EEG and the CG was 1.35 (0.81-2.24, p = 0.743). Conclusions After considerably interfering with exposure during the first year of life, there was a trend towards a higher risk of malaria in the second year in children who had received chemoprophylaxis, but there was no significant rebound. No evidence was found that the age of first exposure to malaria affects the rate of acquisition of NAI. Thus, the timing of administration of antimalarial interventions like malaria vaccines during infancy does not appear to be a critical determinant. Trial registration ClinicalTrials.gov NCT00231452.